2020
DOI: 10.21203/rs.3.rs-58819/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Land use management and carrying capacity of Bangsri Micro Watershed, East Java, Indonesia: a baseline study

Abstract: The increase of unsustainable human activities in watershed areas gave a huge pressure, causing land degradation and reduced the river water quality. This study aimed to describe the land use management and calculate the carrying capacity as a part of natural resource management of Bangsri Micro Watershed, the upper Brantas watershed in East Java, Indonesia. Data was gathered from five villages through interviews, questionnaires, and focus group discussions with multiple stakeholders. In addition, data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In reality very little attention has been researched to the spatial variability of soils for agricultural activities in a broad sense [3,4,5]. Soil heterogeneity was usually not considered to determine the level of soil fertility or soil quality, but the reality in the fields showed that crop production was uneven due to the spatial variability of soils [6,7]. Spatial variability of soils in the fields directly affected agriculture performance, and will become a major problem in production if spatial variability of soils was ignored or not considered [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In reality very little attention has been researched to the spatial variability of soils for agricultural activities in a broad sense [3,4,5]. Soil heterogeneity was usually not considered to determine the level of soil fertility or soil quality, but the reality in the fields showed that crop production was uneven due to the spatial variability of soils [6,7]. Spatial variability of soils in the fields directly affected agriculture performance, and will become a major problem in production if spatial variability of soils was ignored or not considered [8,9,10].…”
Section: Introductionmentioning
confidence: 99%